Comparison of selected aspects of strength conditioning among junior boulderers and speed and lead climbers - Sas-Nowosielski, K.; Gutek, M. (Journal of Kinesiology and Exercise Sciences, 2022)
Background: Comprehensive preparation of climbers for participation in multi-event competitions requires knowledge of the motor characteristics and fitness profiles of successful athletes competing in their individual events. Such knowledge can be used to prepare training programs to prepare for multi-event climbing competitions. The study aimed to compare the fitness profiles of young athletes specializing in different climbing disciplines: lead climbing, speed climbing, and bouldering. Methods: The study included 13 climbers participating in national and international speed climbing, bouldering, and lead climbing competitions. All athletes were members of the junior national team, aged 17.2±1.9 years. The measurements included: rope climbing power test of the upper limbs, upper limb power test on a campus board, the agonist-to-antagonist ratio of upper body strength, bent arm hang test, core strength test, simple and complex reaction time measurements, Margaria-Kalamen stair climb power test, vertical jump, pull-up shoulder endurance test. Results. There were no significant differences between the groups. However, for effect sizes, large values of Cohen`s d were reported in the campus board power in which speed climbers reached the highest results and in the pull-up test with stops in which boulderers scored highest. Small-to-medium effect sizes were observed also in the rope climb test and simple reaction time measurements in which speed climbers scored higher than lead climbers and boulderers, and in prone plank in which speed climbers scored lowest. Conclusions. Speed climbers generated higher power of the lower limbs and had shorter simple reaction times, while boulderers had greater strength in mixed dynamic-static conditions. However, in most strength and conditioning parameters, juniors specializing in different climbing disciplines did not differ significantly.